Wittgenstein on Solipsism in the 1930s: Private Pains, Private Languages, and Two Uses of 'I'. (3rd July 2018) - Button, Tim
Abstract: In the early-to-mid 1930s, Wittgenstein investigated solipsism via the philosophy of language. In this paper, I want to reopen Wittgenstein's 'grammatical' examination of solipsism. Wittgenstein begins by considering the thesis that only I can feel my pains. Whilst this thesis may tempt us towards solipsism, Wittgenstein points out that this temptation rests on a grammatical confusion concerning the phrase 'my pains'. In§1, I unpack and vindicate his thinking. After discussing 'my pains', Wittgenstein makes his now famous suggestion that the word 'I' has two distinct uses: a subject-use and an object-use. The purpose of Wittgenstein's suggestion has, however, been widely misunderstood. I unpack it in§2, explaining how the subject-use connects with a phenomenological language, and so again tempts us into solipsism. In §§3 –4, I consider various stages of Wittgenstein's engagement with this kind of solipsism, culminating in a rejection of solipsism (and of subject-uses of 'I') via reflections on private languages.